IMPLEMENTASI METODE SPEECH RECOGNITION DALAM AL QURAN DIGITAL UNTUK MENINGKATKAN PELAFALAN - Dani Pradana Kartaputra; Fina Kharisma Silviani; Abdurrahman (LPPM STMIK Bandung, 2024)
Enhancing the pronunciation proficiency of the Quran is of paramount importance in comprehending its content. Pronunciation errors can alter the meaning of Quranic verses, making accurate pronunciation a key to the correct understanding of Islamic teachings, particularly the Quran. Through the implementation of speech recognition methods in a digital Quranic application, individuals are aided in correctly reciting Quranic verses, thus providing an interactive learning medium. In this research, the author developed data using Neural Networks algorithms that mimic the way the human brain processes and retains information. The results of this study demonstrate that the utilization of speech recognition technology in Quranic learning can significantly improve pronunciation skills. It is hoped that this application can serve as a supportive system facilitating Quranic education.